Pelatihan Pemanfaatan Google Play Store sebagai Media Promosi dan Pemasaran Produk UMKM di Desa Singajaya Kabupaten Indramayu - Agus Yudianto; Taufansyah Firdaus; Nana Supriatna Sonjaya; Meddy Nurpratama (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
This community service program aimed to improve the capacity of Micro, Small, and Medium Enterprises (MSMEs) in using digital technology as a medium for product promotion and marketing through the Google Play Store platform. The program was conducted in Singajaya Village, Indramayu Regency, employing a participatory approach that covered preparation, training, evaluation, and follow-up mentoring stages. A total of 25 MSME practitioners from various business sectors, including processed food and handicrafts, took part in the program. The results indicated an improvement in participants' understanding of digital marketing, reflected by a 35% increase in the average post-test score compared to the pre-test. Furthermore, 22 participants (88%) successfully created digital promotional accounts and uploaded product information through Android-based applications connected to the Google Play Store. The use of this digital platform proved effective in expanding market reach and increasing the visibility of MSME products, although the effect on sales growth had not yet been observed evenly, as the program remained in its early stage of execution. Key success factors included strong participant enthusiasm and support from the village government, while the primary challenges were limited digital literacy and unstable internet access. Based on these findings, continued assistance programs are strongly recommended, including advanced digital marketing training, periodic monitoring of application usage, and strengthened collaboration with the village government and MSME communities to sustain digital technology adoption and achieve greater economic outcomes.